2009
DOI: 10.1371/journal.pone.0006237
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis and Expression Patterns of Odorant-Binding Proteins from the Southern House Mosquito Culex pipiens quinquefasciatus

Abstract: Olfactory-based behaviors in mosquitoes are mediated by odorant-binding proteins (OBPs). They form a multigenic family involved in the peripheral events in insect olfaction, specifically the transport of odorants to membrane-bound odorant receptors. OBPs contribute to the remarkable sensitivity of the insect's olfactory system and may be involved in the selective transport of odorants.We have employed a combination of bioinformatics and molecular approaches to identify and characterize members of the “classic”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 49 publications
2
89
0
Order By: Relevance
“…In conclusion, our findings demonstrate that the empty neuron system in the ab3 basiconic sensilla of D. melanogaster has some limitations for testing ORs from species of a distant taxon (e.g., Lepidoptera vs. Diptera), although this mutant fruit fly was an enormously successful surrogate for D. melanogaster (10, 11) as well as mosquito ORs (16), probably because flies and mosquitoes, both in the order Diptera, harbor related odorant-binding proteins (21,22). We then tested BmorOR1 in the trichoid sensilla of the fruit fly, which already has a biochemical machinery for the detection of the fruit fly sex pheromone (23,24).…”
Section: Bombykol Elicits Significantly Higher Responses In Flies Thamentioning
confidence: 97%
“…In conclusion, our findings demonstrate that the empty neuron system in the ab3 basiconic sensilla of D. melanogaster has some limitations for testing ORs from species of a distant taxon (e.g., Lepidoptera vs. Diptera), although this mutant fruit fly was an enormously successful surrogate for D. melanogaster (10, 11) as well as mosquito ORs (16), probably because flies and mosquitoes, both in the order Diptera, harbor related odorant-binding proteins (21,22). We then tested BmorOR1 in the trichoid sensilla of the fruit fly, which already has a biochemical machinery for the detection of the fruit fly sex pheromone (23,24).…”
Section: Bombykol Elicits Significantly Higher Responses In Flies Thamentioning
confidence: 97%
“…The sequencing of the Cx. quinquefasciatus genome has almost been completed (Pelletier andLeal 2009, Waterhouse et al 2008). A large family of olfactory receptor genes (ORs) and gustatory receptor genes (GRs) has been identified (Van der Goes van Naters and Carlson 2006).…”
Section: Van Der Goes Van Naters and Carlson 2006)mentioning
confidence: 99%
“…For example, mechanisms that affect the expression of olfactory genes in mosquitoes can now be studied in detail, allowing for a comprehensive understanding of the insect response to selected odorants (Touhara and Vosshall 2009, Chapter 2 in this volume). In addition, recent data on odorant binding proteins (OBPs) demonstrate the significance of these molecules in transporting volatile chemicals through the sensillum fluid to the receptor membrane, but also how gene silencing, using RNAi technologies, can fundamentally alter these processes, suggesting behavioural changes that went hitherto unexplained (Pelletier and Leal 2009, Zhou et al 2008. The challenge is how this information can be maximally exploited for vector-borne disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Several OBPs have been isolated and cloned from Culex spp. (7)(8)(9), and CquiOBP1 has been mapped to a specific sensilla type on antenna, and functional studies showed binding of this OBP to semiochemicals involved in the chemical ecology of this mosquito species (10).…”
mentioning
confidence: 99%